Cloud Pattern Analysis Using AI and Machine Learning from Satellite Images - M. Sravani; K.Krishna Murthy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud patterns play a critical role in understanding atmospheric processes, influencing weather systems, climate patterns, and environmental changes. The analysis of cloud formations using satellite imagery has become a cornerstone in meteorological and climate studies, aiding in weather prediction, storm tracking, and monitoring long-term climate changes. Clouds impact the Earth’s energy balance by modulating solar radiation and trapping heat, making their accurate analysis essential for understanding both short-term weather fluctuations and broader climate phenomena. However, analyzing cloud patterns poses significant challenges due to the complexity of cloud formations, their diverse types, and the influence of dynamic environmental factors such as temperature, humidity, and wind currents. Satellite imagery, with its high spatial and temporal resolution, provides an invaluable source of data for studying clouds globally, but the large volume of data generated requires efficient and automated approaches for interpretation. Cloud pattern analysis plays a pivotal role in advancing weather forecasting, climate change monitoring, and environmental research. They often fail to model fine-grained spatial variations effectively, incur high computational costs, and face challenges such as overfitting, data scarcity, and class imbalance. These limitations hinder their ability to deliver reliable and scalable solutions for real-time applications. Existing systems struggle with limited accuracy in complex scenarios, an inability to capture spatial variations effectively, high computational costs, overfitting issues, and insufficient generalization Considering these challenges, we propose a hybrid deep learning framework that integrates CNNs for spatial feature extraction with U-Net++, a powerful segmentation-based model designed to enhance cloud pattern recognition. This automated, robust, and scalable approach leverages AI and machine learning advancements to analyze satellite images effectively. It addresses diverse cloud types, adapts to varying environmental conditions, and processes large datasets in real-time, providing highly accurate cloud behavior predictions. The proposed methodology improves precision and generalization in cloud pattern analysis, offering a transformative solution for real-world meteorological and environmental applications.